Pulsed Laser Deposition of Epitaxial ZnSxSe1-x Thin Films for Waveguiding Applications in Mid-IR Active Multilayered Structures. (8th February 2017) - Lindsey, Zachary R.; Rhoades, Matthew W.; Fedorov, Vladimir V.; Mirov, Sergey B.; Camata, Renato P.
ABSTRACT: Chromium doped II-VI semiconductors (such as ZnSe and ZnS) feature broad mid-IR emission in the 2-3 μm spectral range due to intershell transitions of the Cr 2+ ions. These materials show much promise for development of a tunable, electrically-pumped, mid-IR laser source. For integration into a mid-IR active multilayered structure, the ternary alloy ZnSx Se1-x is an attractive waveguiding material due to its lattice-matching ability and lower index of refraction with respect to the Cr 2+ :ZnSe active material. Epitaxial growth of each layer is desired to achieve the electronic and optical properties necessary for successful integration into a lasing device, so a study was conducted on the effects of sulfur content and growth temperature on the crystal quality of the resulting thin films. Several films of ZnSx Se1-x were deposited by pulsed laser deposition (PLD) using a 248 nm KrF excimer laser source at varying growth temperatures and with various compositional parameters onto (100) GaAs substrates. The samples were analyzed via x-ray diffraction (XRD) and energy dispersive x-rays (EDX) to investigate the crystal quality and elemental content of the films for device integration. Film-substrate epitaxy was achieved and upper bounds to the defect density were calculated for several regimes of compositional parameter and growth temperature. From all samples produced, the lowest defect density of 2.2 x 10 10 cm -2 was observed for the x=0.06 film grown at 450°C, while the lowest lattice mismatch between the substrate and epilayer of 0.059% was observed for the x=0.02 film grown at 450°C.